Do Country-level Investor Protections Affect Security-level Contract Design? Evidence from Foreign Bond Covenants - Miller, Darius P.; Reisel, Natalia (Review of Financial Studies, 2012)
[This article studies the ability of security-level contracts to substitute for poor countrylevel investor protections. Using a cross-country sample of restrictive covenants, we find that bond contacts are more likely to include covenants when creditor protection laws are weak. Further, the use of restrictive covenants in weak creditor protection countries is associated with a lower cost of debt. We also find that strong country-level shareholder rights are not necessarily harmful to bondholders. Overall, the findings suggest that issuers and investors can create international contracts that overcome some of the deficiencies of country-level investor protections and facilitate access to external finance.]